PAP TESTING AMONG VIETNAMESE WOMEN: HEALTH CARE SYSTEM AND PHYSICIAN FACTORS - Taylor, Victoria M. (2004)
Cervical cancer occurs more frequently among Vietnamese Americans than women of any other race/ethnicity. In addition, previous studies in California have documented low Papanicolaou (Pap) testing rates in Vietnamese communities. This study focused on health care system factors and physician characteristics associated with recent cervical cancer screening among Vietnamese women. A population-based survey was conducted in Seattle during 2002. In-person interviews were conducted by bilingual, bicultural female survey workers. The survey response rate was 82% and 518 women were included in the analysis. Seventy-four percent of the respondents reported having been screened for cervical cancer on at least one occasion, and 64% reported a Pap smear within the previous 2 years. Women with a regular doctor were more likely to have been recently screened than those without a regular doctor (OR = 2.33, 95% CI = 1.45–3.74). Among those with a regular doctor, having a male physician, receiving care at a private doctor’s office (rather than a community, hospital, or multi-specialty clinic), and concern about the cost of health care were independently associated with lower screening rates. Physician ethnicity was not associated with recent Pap smear receipt. The findings support targeted interventions for Vietnamese women without a regular physician and private doctors’ offices that serve Vietnamese Americans. The availability of low cost screening services should be publicized in Vietnamese communities.